2021
DOI: 10.1016/j.gocm.2021.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcomes after fertility preservation in women with endometrial carcinoma and atypical endometrial hyperplasia: A systematic review and meta-analysis

Abstract: ObjectiveThe objective of the study was to compare the effects of assisted reproductive technology (ART) and spontaneous pregnancy on pregnancy outcomes in women with endometrial carcinoma (EC) and atypical endometrial hyperplasia (AEH) following fertility-sparing treatments.MethodsRelevant studies published through July 2020 were identified from PubMed and Web of Science literature searches. The pregnancy outcomes of ART and spontaneous pregnancy were summarized and compared for women with complete remission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…A clinical pregnancy will be defined as at least one intrauterine pregnancy sac with yolk sac or original cardiac pulsations on a B-ultrasound examination. A live birth will be defined as the birth of a healthy infant not requiring admission to the neonatal intensive care unit, at 28 weeks gestation or more, during the follow-up period [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…A clinical pregnancy will be defined as at least one intrauterine pregnancy sac with yolk sac or original cardiac pulsations on a B-ultrasound examination. A live birth will be defined as the birth of a healthy infant not requiring admission to the neonatal intensive care unit, at 28 weeks gestation or more, during the follow-up period [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…In a retrospective study of 107 AEH/EC patients by Xiao Zerui et al. ( 21 ), the pregnancy rate was 37.5% in patients with comorbid diabetes mellitus and 40.9% in patients with comorbid IR. The above data suggest a less favorable pregnancy rate in AEH/EC patients with combined MetS.…”
Section: Factors Affecting Pregnancy Outcomes Of Art Treatment In Aeh...mentioning
confidence: 99%
“…In a retrospective study of 107 AEH/EC patients, Xiao Zerui et al. ( 21 ) showed that the clinical pregnancy rate in patients with uterine adhesions was lower than that in patients without it. Elizur et al.…”
Section: Factors Affecting Pregnancy Outcomes Of Art Treatment In Aeh...mentioning
confidence: 99%
“…She was given a levonorgestrelreleasing intrauterine device (LNG-IUD) as the maintenance treatment and a referral to a reproductive specialist. Two months after CR, IVF-ET was recommended for her due to the high pregnancy rate than spontaneous pregnancy in EC [3] . Her anti-mullerian hormone (AMH) was 3.528ng/ml, serum basic folliclestimulating hormone (FSH) was 7.62IU/L, and antral follicle count (AFC) was 13, then ovarian reserve was normal.…”
Section: Case Reportmentioning
confidence: 99%
“…Preoperative chemotherapy can also be recommended to reduce tumor focus of which the preferred regimens include carboplatin and paclitaxel [2] . This complicated treatment should be formulated after a comprehensive preoperative discussion with the multi-disciplinary team (MDT) [3] .…”
Section: Introductionmentioning
confidence: 99%